Does sexual dimorphism vary by population? Laryngeal and ear anatomy in cricket frogs. Issue 3 (8th November 2018) - McClelland, Blinda E; Ryan, Michael J; Wilczynski, Walter
Abstract: Acoustic communication in many anuran species can show the effects of both natural and sexual selection. This is reflected in the sexually dimorphic anatomy of the larynx and ear structures, as well as the allometric relationship of these morphological traits to head or body size. In this study, we examined laryngeal and ear structures of cricket frogs Acris crepitans not only as sexually dimorphic characteristics, but also as they differ across populations in environmentally different habitats. We used 2-way ANOVA to determine whether the volumetric or linear measurements of these structures differed by sex and population. Females have significantly larger body, head, and ear sizes, but significantly smaller larynges than males. Furthermore, females as well as males show larger body and head sizes, ears, and larynges in a dryer open habitat. An ANCOVA analysis shows that males, but not females, differ in laryngeal size across populations beyond the allometric changes attributable to head size alone indicating that males have a greater degree of laryngeal population variation. In contrast, our covariate analysis found that in both sexes many of the ear differences are non-significant once head size is accounted for, suggesting that most of the population-level ear variation is due to allometric effects of body size. We conclude that although both sexes show size differences in the larynx related to selection for larger body size in dry, open habitats, selection on males for larger larynx size related to the production of lower frequency calls in those habitats does not result in correlated changes in the female larynx. The results suggest that in anurans, selection for changes in body and head size affects both sexes equally, male calls and the vocal structures responsible for them can further diversify without concordant changes in females.